Performing Oti-bharan ritual - Mumbai Archive Project Team (Jio Institute, 2024)
The oti-bharan ritual is performed by a team of five married women in the family. Four women hold the ends of a rectangular piece of cloth, symbolizing of the womb (oti in Marathi).